2009
DOI: 10.1242/jeb.028027
|View full text |Cite
|
Sign up to set email alerts
|

The importance of color in mate choice of the blue crab Callinectes sapidus

Abstract: SUMMARYVisual displays often play a large role in animal communication, particularly in sexual interactions. The blue crab Callinectes sapidus is both colorful and highly visually responsive, yet almost all studies of their courtship have focused on chemical cues. In the blue crabʼs underwater environment, however, visual cues may function more rapidly and over a longer distance than chemical cues. Given that blue crabs are aggressive and cannibalistic, visual cues may therefore allow blue crabs to quickly eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 42 publications
4
34
0
Order By: Relevance
“…Previous behavioral experiments have indicated that male blue crabs use chromatic cues when choosing a female mate by demonstrating male preference for red-clawed females over those with gray claws matched in relative luminance (Fig.6B) (Baldwin and Johnsen, 2009). It remained unclear, however, whether males would be capable of discriminating between female claw colors found in nature (Fig.1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous behavioral experiments have indicated that male blue crabs use chromatic cues when choosing a female mate by demonstrating male preference for red-clawed females over those with gray claws matched in relative luminance (Fig.6B) (Baldwin and Johnsen, 2009). It remained unclear, however, whether males would be capable of discriminating between female claw colors found in nature (Fig.1).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for easier comparison we normalized all crab-perceived luminance by the perceived luminance of the red test color used in the behavioral experiments described below, referring to this ratio as 'relative luminance'. To determine color as perceived by the blue crab eye, we assumed that color vision occurred via an opponency mechanism between the putative 440nm and a 508nm pigment in the blue crab eye (Martin and Mote, 1982;Baldwin and Johnsen, 2009). We used a simple model that assumes that the influence of the two pigments is balanced over the wavelength range of 400 to 700nm, i.e.…”
Section: Measuring Spectral Reflectance Of Claw Colormentioning
confidence: 99%
See 2 more Smart Citations
“…Visual perception provides an important source of information for many animals to find food and mates, detect potential predators and threats, and notice changes in their surroundings (Baldwin and Johnsen, 2009;Kinoshita and Arikawa, 2014). Color and shape are two reliable and useful dimensions in visual signals.…”
Section: Introductionmentioning
confidence: 99%